Spirals of Nature: Geometry, Growth, and the Dance of Entropy - Belay Sitotaw Goshu (Britain International for Academic Research (BIAR) Publisher, 2026)
The concept of pasta serves as a unique lens to explore the interplay of physics and biology across scales, from everyday phenomena to cosmic events. This study integrates three phenomena spaghetti breaking, nuclear pasta in neutron stars, and spiral patterns in biological systems to illustrate fundamental principles like elasticity, wave propagation, extreme matter, and biological optimization. The purpose was to develop a unified computational framework to demonstrate how pasta bridges physics and biology, providing educational insights. Three simulations were conducted using Python. Spaghetti breaking was modeled as a 1D elastic rod, solving the wave equation to study stress wave propagation. Nuclear pasta was simulated via molecular dynamics, modeling 100 nucleons to identify gnocchi, spaghetti, and lasagna phases. Spiral patterns were generated using Vogel’s (1979) phyllotaxis model (r=c√n,θ=n∙〖137.5〗^o for 500 seeds, comparing their density to a circular arrangement. The spaghetti-breaking simulation showed stress waves causing multiple fractures, with 5.00 Joules of elastic energy released. Nuclear pasta exhibited a shear modulus of 1.23×1020 Pa, highlighting its role in gravitational wave production. The spiral simulation achieved a 15.22% density increase (bounding circle). Pasta effectively unifies physics and biology, offering a valuable educational tool despite density calculation discrepancies. Adjust parameters like c or the number of seeds in the spiral simulation and enhance models to 3D for accuracy.